A Patent-Pending Ointment Containing Extracts of Five Different Plants Showed Antinociceptive and Anti-Inflammatory Mechanisms in Preclinical Studies - Juan Carlos Barragan-Galvez; Maria Leonor Gonzalez-Rivera; Juan C. Jiménez-Cruz; Araceli Hernandez-Flores; Guadalupe de la Rosa; Martha L. Lopez-Moreno; Eunice Yañez-Barrientos; Michelle Romero-Hernández; Martha Alicia Deveze-Alvarez; Pedro Navarro-Santos; Claudia Acosta-Mata; Mario Alberto Isiordia-Espinoza; et al. (MDPI AG, 2024)
Background/Objectives: The antinociceptive and anti-inflammatory effects of a patent-pending ointment containing plant extracts from Eucalyptus globulus, Curcuma longa, Hamamelis virginiana, Echinacea purpurea, and Zingiber officinale were evaluated. Methods: Plant extracts were chemically characterized by gas chromatography-mass spectroscopy. The antinociceptive activity of the ointment was assessed using the hot plate, tail flick, and formalin tests, whereas the anti-inflammatory activity was measured using the acute and chronic TPA-induced ear edema tests. Mechanisms of action were evaluated using inhibitors from signaling pathways related to pain response and by using histological analysis and assessing the expression and activity of pro-inflammatory mediators. Results: The ointment showed antinociceptive and anti-inflammatory effects like those observed with diclofenac gel (1.16% v/v) and ketoprofen gel (2.5% v/v). The antinociceptive actions of the ointment are mediated by the possible participation of the opiodergic system and the nitric oxide pathway. The anti-inflammatory response was characterized by a decrease in myeloperoxidase (MPO) activity and by a reduction in ear swelling and monocyte infiltration in the acute inflammation model. In the chronic model, the mechanism of action relied on a decrease in pro-inflammatory mediators such as COX-2, IL-1β, TNF-α, and MPO. An in-silico study with myristic acid, one of the compounds identified in the ointment's plant mixture, corroborated the in vivo results. Conclusions: The ointment showed antinociceptive activities mediated by the decrease in COX-2 and NO levels, and anti-inflammatory activity due to the reduction in IL-1β and TNFα levels, a reduction in MPO activity, and a decrease in NF-κB and COX-2 expression.